TWO TRUTHS IN SUNDANESE SCRIPT CARIOS TAMIM - Rohim . (Humaniora, 2014)
This article aims to describe the Sundanese manuscript of wawacan Carios Tamim by way of editing its text and analyzing its structure.Besides, this article also explores how, by applying the actant theory and functional model promoted by Greimas, the events are sequentially related through the characters. From the analysis, it can be seen that the formal structure of Carios Tamim contains 14 pupuh in 390 couplets and 2644 lines in three elements of story making, i.e. the manggala (preliminary), the content of the story, and the ending. Meanwhile, the analysis of its narrative structure shows that Carios Tamim has the plot, the characters, the characterization, and the setting so closely related that they build up the theme of the story, i.e. raising a truth out of two truths. The truth as revealed in Carios Tamim is strongly concerned with the munakahat (marriage). On the ground of Greimas’ actant theory and functional model, the character Tamim Ibnu Habib Ad-Dāri and his wife as subjects are successfully managed to get on the object owing to the events they are experiencing are closely related one another in a causal relationship.